Preparation of thin-film-composite polyamide membranes for desalination using novel hydrophilic surface modifying macromolecules - Abu Tarboush, Belal (University of Ottawa (Canada), 2009)
Reverse osmosis (RO) by polymeric membranes is known to be the most successful technology for brackish and seawater desalination processes. For the development of these polymeric RO membranes, two different techniques have been used: The phase inversion method for asymmetric membranes, such as cellulose acetate (CA) membrane and the interfacial polymerization for thin film composite (TFC) membranes. Polyamide composite membranes which are characterized by a thin film supported on a chemically different asymmetric porous membrane have become commercially successful for certain applications, especially for seawater desalination. Although TFC aromatic polyamide membrane has excellent characteristics and performance among other types of RO membranes, it suffers from some drawbacks such as biofouling and fouling caused by chemical foulant such as natural organic matter (NOM). The objective of this work is to present a new concept for the preparation of thin-film-composite (TFC) reverse osmosis (RO) membrane by interfacial polymerization on porous polysulfone (PS) support using novel additives. Hydrophi lic surface modifying macromolecules (LSMM) were synthesized both ex-situ by conventional method (cLSMM), and in-situ within the organic solvent of the TFC system (iLSMM). The effects of these LSMMs on the fouling of the TFC RO membranes used in the desalination processes were studied. Fourier transform infrared (FTIR) results indicated that both cLSMM and iLSMM were present in the active layer of the TFC membranes. Scanning electron microscopy (SEM) micrographs depicted that heterogeneity of the surface increases for TFC membranes compared to the control PS membrane, and that higher concentrations of LSMM provided smoother surface. Atomic force microscope (AFM) characteristic data presented that the surface roughness of the skin surface increases for TFC membranes compared to the control. The RO performance results showed that the addition of the cLSMM significantly decreased the salt rejection of the membrane and slightly reduced the flux, while in the case of the iLSMM, salt rejection was improved but the flux declined at different rates for different iLSMM concentrations. The membrane prepared by the iLSMM exhibited less flux decay over an extended operational period.
Keywords: Engineering, Chemical.